The Maintenance of the Javanese Language Among Migrant Communities in Pangkajene Sub-district, Maritengngae District - Rusny Edy; M. Nurzin R. Kasau; Muhammad Hanafi; Saifullah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to describe the forms, strategies, and supporting and inhibiting factors for maintaining the Javanese language in the diaspora community in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency. The phenomenon of language shift that occurs due to social mobility and interaction with different language environments is the background to the importance of this study. The method used in this study is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the maintenance of the Javanese language is carried out through the use of language in the family, social activities, and religious areas. The strategies applied include passing on the language to children, using Javanese in traditional activities, and getting used to it in daily communication. Supporting factors include a sense of pride in ethnic identity and the existence of a community of fellow diaspora, while inhibiting factors include the dominance of Indonesian and Bugis languages in the surrounding environment and the lack of interest of the younger generation. This study emphasizes the importance of the role of families and communities in maintaining the sustainability of regional languages in a multicultural society.